BEVERAGE PREPARATION FROM FISH HYDROLYSATES. - PRABHU, P. V. PRABHU V; RADHAKRISHNAN, A G; JAMES, M ARUL (Fishery Technology, 2017)
A method for the preparation of energy food incorporatingfish hydrolysates, sugar, cocoa, malt extract etc. is described.The product has good consumer appeat The preparation doesnot impart any bitter taste of the hydrolysate to the finalproduct irrespective of the type of fish used for preparingthe hydrolysate. It freely mixes with hot or cold milk and theresulting drink is adjudged to be very palatable.